2015
DOI: 10.5194/amt-8-471-2015
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automated system for quantifying the oxidative potential of ambient particles in aqueous extracts using the dithiothreitol (DTT) assay: results from the Southeastern Center for Air Pollution and Epidemiology (SCAPE)

Abstract: Abstract. A variety of methods are used to measure the capability of particulate matter (PM) to catalytically generate reactive oxygen species (ROS) in vivo, also defined as the aerosol oxidative potential. A widely used measure of aerosol oxidative potential is the dithiothreitol (DTT) assay, which monitors the depletion of DTT (a surrogate for cellular antioxidants) as catalyzed by the redox-active species in PM. However, a major constraint in the routine use of the DTT assay for integrating it with large-sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
160
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(186 citation statements)
references
References 45 publications
(59 reference statements)
15
160
3
Order By: Relevance
“…Higher wintertime DTT activity has been frequently reported [9,24,26,27,36,53], on the contrary, other studies found higher activity in summer as compared to winter [31,44,47].…”
Section: Seasonal and Spatial Variationsmentioning
confidence: 75%
“…Higher wintertime DTT activity has been frequently reported [9,24,26,27,36,53], on the contrary, other studies found higher activity in summer as compared to winter [31,44,47].…”
Section: Seasonal and Spatial Variationsmentioning
confidence: 75%
“…One of the important pathways leading to deleterious impacts on health is believed to be induced oxidative stress by the generation of reactive oxygen species (ROS), through the interaction of particulate matter with the human lung (Donaldson et al, 2002). Reactive oxygen species denote chemically reactive molecules containing oxygen (e.g., radicals, oxygen ions and peroxides including the OH radical, the O − 2 radical, H 2 O 2 or organic peroxides) (Fuller et al, 2014;Sagai et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many acellular assays exist for the determination of ROS quantities in particles, including dithiothreitol (DTT) (Fang et al, 2015) and 2 ,7 -dichlorofluorescin (DCFH) (Fuller et al, 2014;King and Weber, 2013;Wang et al, 2011). The DCFH assay is one of the most commonly used assays today.…”
Section: Introductionmentioning
confidence: 99%
“…Various assays have been developed to study PM-induced oxidant production, including cell-free chemical assays that measure the oxidative potential of PM samples (Kumagai et al, 2002;Cho et al, 2005;Fang et al, 2015b) as well as cellular assays that measure intracellular ROS/RNS produced as a result of PM exposure (Landreman et al, 2008;Tuet et al, 2016). Cell-free assays simulate biologically relevant redox (reduction-oxidation) reactions using an antioxidant species (e.g., dithiothreitol, DTT; ascorbic acid, AA).…”
Section: W Y Tuet Et Al: Inflammatory Responses To Soa Generated Fmentioning
confidence: 99%
“…5;Tuet et al, 2016). These ambient samples were analyzed using the same methods for determining oxidative potential (DTT assay; Cho et al, 2005;Fang et al, 2015b) and ROS/RNS production (cellular carboxy-H 2 DCFDA assay; Tuet et al, 2016). Furthermore, the same extraction protocol (water-soluble extract) was followed in both studies (Tuet et al, 2016).…”
Section: Comparison With Ambient Datamentioning
confidence: 99%